The Effect of Saving Products Promotion Strategy and Quality of Services on Saving Decisions in Bni Tasikmalaya - Wursan; Tine Badriatin (Enrichment : Journal of Management, 2022)
The background of this research is where a survey conducted by Top Brand, for 5 years in a row BNI always gets the first rank compared to other banks. This shows that the decision to save at Bank BNI is very high compared to other banks such as Bank BRI, Bank BJB, and Bank Mandiri. Where the presentation obtained shows that the customer's decision to save at BNI Bank since 2016-2021 seen from the number of savings has increased from year to year, but the increase has fluctuated. In 2020 the increase was only 1,624 customers, lower than the previous year, and the highest increase in the number of customers occurred in 2021. The decision to save BNI KC Tasikmalaya customers still needs to be improved, considering that the decision is the end of a treatment, so it can determine the success of a program or ideas. Thus, the formulation of the problem in this study is how does the promotion strategy of savings products affect the decision to save at BNI KC Tasikmalaya? How does the promotion strategy of savings products and service quality affect the decision to save at BNI KC Tasikmalaya? While the research method used in this study is explanatory research, namely research used to explain causal relationships between variables through hypothesis testing which is formulated or often referred to as explanatory research. This study is a research conducted to determine the effect of the promotion strategy of savings products and service quality on the saving decisions of BNI KC Tasikmalaya customers.